Analisis Kesulitan Guru Pembimbing dalam Menguasai Konsep dan Praksis Assesment - Citra Abriani Maharani; Muswardi Rosra; Yusmansyah Yusmansyah; Diah Utaminingsih (JURNAL INOVATIF ILMU PENDIDIKAN, 2019)
This research aimed to determine the level of difficulty of the Supervising Teacher in Mastering the Concept and Praxis of Assessment to Understand the Conditions, Needs, and Problems of the Counselee. This research used survey research methods with descriptive quantitative research. The population of the research was 160 guidance and counseling teachers who were taken by using proportional sampling techniques from each regional representative, so that 50 teachers of guidance and counseling were obtained. The data collection is collected through understanding tests. The data analysis is used descriptive quantitative analysis. The results of the study showed that the Level of Teacher Difficulties in Mastering the Concept and Praxis of Assessment to Understand the Conditions, Needs, and Problems of the counselees in the very low category with a percentage of 44%. This is supported by the results of the respondents' justification analysis that the level of understanding of the concepts and assessment praxis in guidance and counseling teachers in schools is in the moderate category with only 16%.Keywords: counselor competence, assessment, mastery of concept and prescriptive assessment, teacher guidance and counselingDOI: http://dx.doi.org/10.23960/jiip.v1i2.18032